Impact of ESPGHAN no-biopsy strategy on the outcome of celiac disease treatment in children - Iulia Enache; Iulia Enache; Mariana Jinga; Mariana Jinga; Alexandra Palaga; Daniel Vasile Balaban; Daniel Vasile Balaban; Felicia Galos; Felicia Galos; Dhea-Maria Macovei; Alina Popp; Alina Popp; et al. (Frontiers in Pediatrics)
AimThe European Society for Pediatric Gastroenterology Hepatology and Nutrition (ESPGHAN) allows a no-biopsy diagnostic of celiac disease under certain conditions. We assessed the impact of the diagnostic algorithm on the patient's long-term outcome by comparing the serology-based diagnosed patients to biopsy-proven ones.MethodsWe reviewed the charts of children presenting with antitransglutaminase IgA titers above ten times upper limit of normal and consecutively diagnosed with celiac disease between 2010 and 2014, a time-period overlapping with ESPGHAN diagnostic guideline change in 2012. Outcome measures for no-biopsy vs. biopsy-proven diagnosed patients were clinical and laboratory findings, compliance to gluten-free diet and to regular visits after one, two and 8–10 years of follow-up.ResultsClinical and laboratory, i.e., serum chemistry and autoantibody outcome measures on gluten-free diet clearly showed worse patient healing in the 33 serology-based diagnosed children compared to the 30 biopsy-proven ones. The attendance of the follow-up visits was also higher in the biopsy group.ConclusionsOur results indicate that dietary transgressions are common in childhood celiac disease resulting in slow healing. Therefore, there is a need of improvement of the management, with special attention regarding the ESPGHAN no-biopsy criteria diagnosed patients. Our study also indicates that novel treatments adjunctive to diet are warranted in children.